Answer:
Emma can play for more than one minute.
Step-by-step explanation:
1/4 is the same as 2/8 because 1/4*2=2/8.
2/8 is much smaller than 7/8.
Emma can play for 3 1/2 minutes in total.
friends. Keychains cost $2 each, and refrigerator magnets cost $1
each. Let x represent the number of keychains that Rosa bought,
and let y represent the number of refrigerator magnets.
Rosa bought 12 items and paid $18 more for the keychains than
for the refrigerator magnets.
9514 1404 393
Answer:
Step-by-step explanation:
We assume you want to know how many of each item Rosa bought.
The problem information lets us write two equations:
x + y = 12
2x - y = 18
Adding the two equations, we get ...
3x = 30
x = 10 . . . . . divide by 3
y = 12 -x = 2 . . . find y
Rosa bought 10 keychains and 2 magnets.
Answer:
Step-by-step explanation:
A square enclosure would have all sides of equal length. Thus, a perimeter of 16 feet would have 4 sides (16/4) or 4 feet in length. The diagonal would form a right triangle with two sides of 4 feet each.
The diagonal, the hypotenuse, is determined by:
4^2 + 4^2 = x^2
32 = x^2
x = 5.6569 feet
The length of the diagonal of the square enclosure is approximately 5.7 feet.
The perimeter of a square is the sum of all its sides. In this case, the square enclosure has a perimeter of 16 feet. Since all the sides of a square are equal in length, we can divide the perimeter by 4 to find the length of one side.
The length of one side of the square is 16/4 = 4 feet.
To find the length of the diagonal of a square, we can use the Pythagorean theorem. The diagonal, the side, and the side form a right triangle, where the diagonal is the hypotenuse. The formula for the length of the diagonal is d = sqrt(2)s, where s is the length of one side of the square.
Substituting the value for s, we have d = sqrt(2) * 4.
Calculating this using a calculator, we get d ≈ 5.7 feet.
#SPJ3
Changes in output are evenly spaced for evenly spaced changes in input, so the rule is linear. Changes in output are 1 for changes in input of 3, so the rule involves a factor of 1/3. One possible rule is
... output = (1/3)·input + 3
If y and x are used to represent output and input, respectively, this is
... y = (1/3)x + 3
Do not include any spaces in your answer. Use parentheses to separate your factors. A sample answer might be (x+1)(x-4).
Answer:
(x-8) (x+7)
Step-by-step explanation:
x^2 -x-56
We want to factor this problem.
What two numbers multiply to negative 56 and add to -1
-8 *7 = -56
-8+7 = -1
We can use -8 and 7
(x-8) (x+7)
Check:
FOIL
first: x*x =x^2
outer: 7x
inner:-8x
last: -8*7 = -56
Add this together
x^2 +7x-8x -56 = x^2 -x-56
Answer:I think it is
7 -5
Step-by-step explanation:
Answer:
D-(7, –5)
Step-by-step explanation:
hope this helps:)